Myanmar in transition: rule of law, democracy, free markets and false contingencies - Fyock, Claiton (AUC Knowledge Fountain, 2015)
Myanmar is in the midst of a major political/economic transition. After years of repressive rule under a harsh military regime, the country is moving towards liberalism. At the behest of the domestic and foreign liberal pressure, the foundations of liberalism including the rule of law, democracy, and open markets are taking shape in Myanmar. This paper demonstrates the lack of agency that Myanmar, both as a state and for the citizens within the state, maintains during this transition. This lack of agency is due, in part, to the neoliberal interpretation of liberalism and its founding tenets. Utilizing Roberto Unger and Susan Marks’s theories of “False Necessity” and “False Contingency,” I will demonstrate how international institutions and ideologies are propagated and forced on Myanmar. The belief in these ideologies and institutions creates pressures and imposes limitations on the systems that they influence in Myanmar. These pressures and limits, in turn, create a lack of true agency in the transition that Myanmar and its people are experiencing. I begin by first exploring the general liberal thought in regards to transition. I then demonstrate the false contingencies that a neoliberal understanding on the liberal tenets reflects. I apply this dynamic to actual circumstances in Myanmar as a case. The thesis concludes with the exploration of the concept of false contingency on Myanmar’s transition to democratization, neoliberalizing markets, and its embrace of human rights.